Impact-resistant packaging material and preparation method thereof

By reacting and melting the loaded zinc oxide porous silica microspheres, phospho-silicon synergistic flame retardant with functionalized polyester and other materials, packaging materials with high impact and antibacterial properties were prepared, and the existing packaging materials were solved. The shortcomings of packaging materials in terms of impact and bacterial growth have significantly improved the transportation and storage safety of goods.

CN119432016AInactive Publication Date: 2025-02-14WUHAN HUANDONG TECHNOLOGY DEVELOPMENT CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411535844.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing packaging materials are difficult to effectively resist impact and bacterial growth during transportation and storage, resulting in damage or deterioration of goods.

Method used

Packaging materials with high impact and antibacterial properties are prepared by reacting and melting the loaded zinc oxide porous silica microspheres, phosphorus-silicon co-effective flame retardant with functionalized polyester.

Benefits of technology

The packaging material exhibits excellent impact resistance in impact testing and significantly improves the storage and transportation safety of goods by inhibiting bacterial growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111520630000041
    Figure BDA0005111520630000041
  • Figure BDA0005111520630000051
    Figure BDA0005111520630000051
  • Figure BDA0005111520630000121
    Figure BDA0005111520630000121
Patent Text Reader

Abstract

The invention discloses an impact-resistant packaging material and a preparation method thereof, and relates to the technical field of packaging materials. When the impact-resistant packaging material is prepared, the zinc oxide-loaded porous silicon dioxide microspheres and the phosphorus-silicon synergistic flame retardant react to prepare functionalized porous silicon dioxide microspheres; the preparation method comprises the following steps: reacting 4-[2, 2 ': 6', 2 ''-terpyridyl]-4 '-yl-benzylamine with ethyl acrylate to prepare a terpyridyl diester monomer; the preparation method comprises the following steps: carrying out condensation polymerization on ethylene glycol, a terpyridyl diester monomer and benzophenone-4, 4 '-diethyl diformate to prepare functional polyester; the functionalized polyester and 2-aminoethyl-2-cyanoacetate are subjected to a reaction, and modified polyester is prepared; and carrying out melt blending on the modified polyester, the functionalized porous silicon dioxide microspheres, zinc chloride and 1, 6-dichlorohexane, and carrying out compression molding to obtain the impact-resistant packaging material. The impact-resistant packaging material prepared by the invention has excellent anti-aging, impact-resistant, flame-retardant and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, in particular to an impact-resistant packaging material and a preparation method thereof. Background Art

[0002] With the rapid development of express delivery and logistics industry, people can buy a wide range of goods through online shopping. However, goods often need to be transported long distances by sea, land and air from the place of shipment to the hands of users. During transportation, goods are often impacted by manual sorting, inertia generated by vehicle transportation, etc. Some electronic products and fragile items may be damaged; a large number of express parcels are piled together, and due to the influence of weather and storage environment, bacteria may breed and mold may occur. Packaging plays an important role in the transportation, storage and stacking of goods. Choosing suitable packaging materials is crucial for the protection of goods. Therefore, it is necessary to develop a packaging material with high impact resistance and antibacterial properties to protect the goods from reaching users safely. Summary of the invention

[0003] The object of the present invention is to provide an impact-resistant packaging material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A shock-resistant packaging material, wherein the shock-resistant packaging material is prepared by reacting porous silica microspheres loaded with zinc oxide and a phosphorus silicon synergistic flame retardant to obtain functionalized porous silica microspheres; polycondensing ethylene glycol, a terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate to obtain functionalized polyester; reacting the functionalized polyester and 2-aminoethyl-2-cyanoacetate to obtain modified polyester; and melt-blending the modified polyester, functionalized porous silica microspheres, zinc chloride, and 1,6-dichlorohexane, and performing compression molding to obtain the shock-resistant packaging material;

[0006] The phosphorus-silicon synergistic flame retardant is prepared by reacting phenyl dichlorophosphate and (9CI)-[(dimethylamino)methyl]-silanediol;

[0007] The porous silica microspheres loaded with zinc oxide are prepared by reacting porous silica microspheres and zinc oxide;

[0008] The terpyridine diester monomer is prepared by reacting 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate.

[0009] A method for preparing an impact-resistant packaging material, the method comprising the following steps:

[0010] (1) Porous silica microspheres and zinc oxide sol are mixed in a mass ratio of 1:(10-12), ultrasonically dispersed for 20-30 min, stirred at 170-180° C. and 300-500 r / min for 1-2 h, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 100-110° C. for 8-10 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; Porous silica microspheres loaded with zinc oxide and anhydrous ethanol are mixed in a mass ratio of 1:(10-12), ultrasonically dispersed for 20-30 min, stirred at 170-180° C. and 300-500 r / min for 1-2 h, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 100-110° C. and 8-10 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; 80-100) were mixed evenly, ultrasonically dispersed for 50-60 min, 1.2-1.4 times the mass of the porous silica microspheres loaded with zinc oxide was added with a phosphorus silicon synergistic flame retardant, 0.07-0.09 times the mass of the porous silica microspheres loaded with zinc oxide was added with dibutyltin dilaurate, and under nitrogen protection, the mixture was stirred at 25-35° C. and 300-500 r / min for 2-3 h, filtered, and dried at 50-60° C. for 16-18 h under vacuum conditions to obtain functionalized porous silica microspheres;

[0011] (2) Ethylene glycol, antimony trioxide, trimethyl phosphate and titanium dioxide are mixed uniformly in a mass ratio of 1:(0.02-0.04):(0.05-0.07):(0.02-0.03), terpyridine diester monomer in an amount of 0.3-0.4 times the molar amount of ethylene glycol and diethyl benzophenone-4,4'-dicarboxylate in an amount of 0.5-0.6 times the molar amount of ethylene glycol are added, and the mixture is placed in a polycondensation reaction kettle for polycondensation reaction. The mixture is cooled to room temperature and then discharged, washed with deionized water for 3-5 times, and dried at 50-60°C for 7-8 hours under vacuum conditions. Prepare functional polyester; mix the functional polyester, 2-aminoethyl-2-cyanoacetate and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.8):(8-10), stir at 80-90°C and 300-500r / min for 10-20min, uniformly add a catalyst solution of 2-2.4 times the mass of 2-aminoethyl-2-cyanoacetate dropwise within 20min, heat to 100-106°C and stir for reaction for 6-7h, dry at 60-70°C under vacuum for 8-10h to prepare modified polyester;

[0012] (3) The modified polyester and the functionalized porous silica microspheres are mixed uniformly in a mass ratio of 1:(0.06-0.08), placed in an internal mixer, stirred at 240-250° C. for 10-12 min, 0.03-0.04 times the mass of the modified polyester zinc chloride and 0.06-0.08 times the mass of the modified polyester 1,6-dichlorohexane are added and mixed uniformly, placed in a mold for compression molding, and demolded after naturally cooling to room temperature to obtain an impact-resistant packaging material.

[0013] As an optimization, the particle size of the porous silica microspheres in step (1) is 200-300 nm and is purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0014] As an optimization, the preparation method of the zinc oxide sol in step (1) is: zinc acetate, diethylene glycol and deionized water are mixed uniformly in a mass ratio of 1: (240-250): (10-12), stirred at 170-180° C. and 300-500 r / min for 5-7 min, cooled to room temperature and then allowed to stand for 2-3 h to obtain the zinc oxide sol.

[0015] As an optimization, the preparation method of the phosphorus-silicon synergistic flame retardant in step (1) is: adding phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol in a molar ratio of 1:1 to acetonitrile with a mass of 18 to 20 times that of phenyl dichloride phosphate, stirring and reacting at 80 to 86° C. and 300 to 500 r / min under nitrogen protection for 5 to 6 hours, and drying at 70 to 80° C. under vacuum conditions for 8 to 10 hours to obtain the phosphorus-silicon synergistic flame retardant;

[0016] The reaction process is:

[0017]

[0018] As an optimization, the preparation method of the terpyridine diester monomer in step (2) is: 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate are uniformly mixed in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene in an amount of 0.03 to 0.05 times the mass of ethyl acrylate is added, and the mixture is stirred at 50 to 60° C. and 300 to 500 r / min for 2 to 3 hours to obtain the terpyridine diester monomer;

[0019] The reaction process is:

[0020]

[0021] As an optimization, the process parameters of the polycondensation reaction in step (2) are: stirring the reaction at 270-280° C. and 300-500 r / min for 1-2 h, reducing the pressure to 50-100 Pa, and continuing the stirring reaction for 1-2 h.

[0022] As an optimization, the preparation method of the catalyst solution in step (2) is: ammonium acetate and glacial acetic acid are mixed evenly in a mass ratio of 1:(3-4) to prepare a catalyst solution.

[0023] As an optimization, the process parameters of the compression molding in step (3) are: at 230-240° C., 2-3 MPa, maintaining pressure for 3-5 min, keeping the pressure constant, cooling to 70-80° C. and maintaining heat for 30-40 min.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] When preparing the impact-resistant packaging material, the present invention comprises the following steps: reacting phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol to obtain a phosphorus-silicon synergistic flame retardant; loading zinc oxide into porous silica microspheres to obtain zinc oxide-loaded porous silica microspheres; reacting the zinc oxide-loaded porous silica microspheres and the phosphorus-silicon synergistic flame retardant to obtain functionalized porous silica microspheres; and reacting 4-[2,2':6',2"-terpyrrolidone] The invention relates to a method for preparing a terpyridine diester monomer by reacting 4'-pyridine-4'-yl-benzylamine and ethyl acrylate; a functional polyester is prepared by polycondensing ethylene glycol, a terpyridine diester monomer and diethyl benzophenone-4,4'-dicarboxylate; a modified polyester is prepared by reacting the functional polyester and 2-aminoethyl-2-cyanoacetate; and the modified polyester, functionalized porous silica microspheres, zinc chloride and 1,6-dichlorohexane are melt-blended and compression molded to prepare an impact-resistant packaging material.

[0026] Firstly, phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol are reacted to obtain a phospho-silicon synergistic flame retardant, and Si-H bonds and tertiary amine structures are introduced into the phospho-silicon synergistic flame retardant; zinc oxide is loaded into porous silica microspheres to obtain porous silica microspheres loaded with zinc oxide; the hydroxyl groups on the porous silica microspheres loaded with zinc oxide react with the Si-H bonds on the phospho-silicon synergistic flame retardant to obtain functionalized porous silica microspheres; phosphorus element, Si-O bonds and tertiary amine structures are introduced into the functionalized porous silica microspheres; the introduction of phosphorus element and Si-O bonds can improve the flame retardant properties of impact-resistant packaging materials; the tertiary amine structure can react with the chlorine on 1,6-dichlorohexane to form a quaternary ammonium salt structure, thereby improving the antibacterial properties of impact-resistant packaging materials; loading zinc oxide in porous silica microspheres can achieve the sustained-release antibacterial effect of zinc oxide.

[0027] Secondly, the amino group on 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine reacts with the carbon-carbon double bond on ethyl acrylate to obtain a terpyridine diester monomer; ethylene glycol, terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate are polycondensed to obtain a functionalized polyester, and a terpyridine structure is introduced into the side chain of the functionalized polyester molecule, and a benzophenone structure is introduced into the main chain of the molecule; the terpyridine structure can complex zinc ions to form a cross-linked network, inhibit the relative slip between molecular chains, and give the impact-resistant packaging material excellent impact resistance; the functionalized polyester The benzophenone structure introduced on the ester reacts with 2-aminoethyl-2-cyanoacetate to obtain a modified polyester, a derivative of the octocrylene structure is generated on the modified polyester molecular chain, and an amino group is introduced; octocrylene belongs to the cinnamic acid compound, and the benzene ring and the carbonyl group in the structure have a conjugated effect, which enables it to effectively absorb medium-wave ultraviolet rays and give the impact-resistant packaging material excellent anti-aging properties; the amino group introduced on the modified polyester molecular chain can also react with 1,6-dichlorohexane to form a cross-linked network, inhibiting the relative slip between molecular chains, and further improving the impact resistance of the impact packaging material. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Embodiment 1:

[0030] A method for preparing an impact-resistant packaging material, the method comprising the following steps:

[0031] (1) Phenyl dichlorophosphate and (9CI)-[(dimethylamino)methyl]-silanediol were added to acetonitrile (18 times the mass of phenyl dichlorophosphate) in a molar ratio of 1:1, stirred at 80°C and 300 r / min for 6 hours under nitrogen protection, and dried at 70°C for 10 hours under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant; zinc acetate, diethylene glycol, and deionized water were mixed at a mass ratio of 1:240:10, stirred at 170°C and 30 r / min for 7 minutes, cooled to room temperature and allowed to stand for 2 hours to obtain a zinc oxide sol; porous silica microspheres and zinc oxide sol were mixed at a mass ratio of 1:10, ultrasonically dispersed for 20 minutes, and dried at 170°C for 10 hours. ℃, 300r / min stirring reaction for 2h, centrifugation, washing with anhydrous ethanol and deionized water for 3 times each, drying at 100℃ for 10h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; the porous silica microspheres loaded with zinc oxide and anhydrous ethanol were mixed evenly at a mass ratio of 1:80, ultrasonically dispersed for 50min, 1.2 times the mass of the porous silica microspheres loaded with zinc oxide as a phosphorus silicon synergistic flame retardant, 0.07 times the mass of the porous silica microspheres loaded with zinc oxide as dibutyltin dilaurate, stirred at 25℃, 300r / min for 3h under nitrogen protection, filtered, and dried at 50℃ for 18h under vacuum conditions to obtain functionalized porous silica microspheres;

[0032] (2) 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate were mixed evenly in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.03 times the mass of ethyl acrylate) was added, and the mixture was stirred at 50°C and 300 r / min for 3 h to obtain a terpyridine diester monomer; ethylene glycol, antimony trioxide, trimethyl phosphate, and titanium dioxide were mixed evenly in a mass ratio of 1:0.02:0.05:0.02, 0.3 times the molar amount of ethylene glycol was added to the terpyridine diester monomer and 0.5 times the molar amount of ethylene glycol was added to diethyl benzophenone-4,4'-dicarboxylate, and the mixture was placed in a polycondensation reactor, and the mixture was stirred at 270°C and 300 r / min for 3 h. min, stirring and reacting for 2h, reducing the pressure to 50Pa, continuing to stir and react for 2h, discharging after cooling to room temperature, washing with deionized water for 3 times, and drying at 50°C for 8h under vacuum conditions to obtain functionalized polyester; ammonium acetate and glacial acetic acid were mixed evenly at a mass ratio of 1:3 to prepare a catalyst solution; functionalized polyester, 2-aminoethyl-2-cyanoacetate, and N,N-dimethylformamide were mixed evenly at a mass ratio of 1:0.6:8, stirred at 80°C and 300r / min for 20min, and a catalyst solution twice the mass of 2-aminoethyl-2-cyanoacetate was uniformly added dropwise within 20min, the temperature was raised to 100°C, stirring and reacting for 7h, and dried at 60°C for 10h under vacuum conditions to obtain modified polyester;

[0033] (3) The modified polyester and functionalized porous silica microspheres were mixed evenly at a mass ratio of 1:0.06, placed in an internal mixer, stirred at 240°C for 12 min, 0.03 times the mass of the modified polyester zinc chloride and 0.06 times the mass of the modified polyester 1,6-dichlorohexane were added and mixed evenly, placed in a mold, and maintained at 230°C and 2 MPa for 5 min. The pressure was kept constant, cooled to 70°C and maintained for 40 min, naturally cooled to room temperature, and then demolded and taken out to obtain an impact-resistant packaging material.

[0034] Embodiment 2:

[0035] A method for preparing an impact-resistant packaging material, the method comprising the following steps:

[0036] (1) Phenyl dichlorophosphate and (9CI)-[(dimethylamino)methyl]-silanediol were added to acetonitrile (19 times the mass of phenyl dichlorophosphate) in a molar ratio of 1:1, and stirred at 83°C and 400 r / min for 5.5 h under nitrogen protection, and dried at 75°C for 9 h under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant; zinc acetate, diethylene glycol, and deionized water were mixed at a mass ratio of 1:245:11, stirred at 175°C and 400 r / min for 6 min, cooled to room temperature, and then allowed to stand for 2.5 h to obtain a zinc oxide sol; porous silica microspheres and zinc oxide sol were mixed at a mass ratio of 1:11, ultrasonically dispersed for 25 min, and dried at 17 The mixture was stirred at 5°C and 400 r / min for 1.5 h, centrifuged, washed with anhydrous ethanol and deionized water for 4 times each, and dried at 105°C for 9 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; the porous silica microspheres loaded with zinc oxide and anhydrous ethanol were mixed evenly at a mass ratio of 1:90, ultrasonically dispersed for 55 min, 1.3 times the mass of the porous silica microspheres loaded with zinc oxide as a phosphorus-silicon synergistic flame retardant, and 0.08 times the mass of the porous silica microspheres loaded with zinc oxide as dibutyltin dilaurate were added, and under nitrogen protection, the mixture was stirred at 30°C and 400 r / min for 2.5 h, filtered, and dried at 55°C for 17 h under vacuum conditions to obtain functionalized porous silica microspheres;

[0037] (2) 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate were mixed uniformly in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.04 times the mass of ethyl acrylate) was added, and the mixture was stirred at 55°C and 400 r / min for 2.5 h to obtain a terpyridine diester monomer; ethylene glycol, antimony trioxide, trimethyl phosphate, and titanium dioxide were mixed uniformly in a mass ratio of 1:0.03:0.06:0.025, terpyridine diester monomer (0.35 times the molar amount of ethylene glycol) and diethyl benzophenone-4,4'-dicarboxylate (0.55 times the molar amount of ethylene glycol) were added, and the mixture was placed in a polycondensation reactor and stirred at 275°C and 400 r / min. The mixture was stirred and reacted for 1.5 hours, the pressure was reduced to 75 Pa, and the mixture was stirred and reacted for 1.5 hours. The mixture was cooled to room temperature and discharged, and washed with deionized water for 4 times. The mixture was dried at 55°C for 7.5 hours under vacuum conditions to obtain a functionalized polyester. Ammonium acetate and glacial acetic acid were mixed evenly at a mass ratio of 1:3.5 to prepare a catalyst solution. The functionalized polyester, 2-aminoethyl-2-cyanoacetate, and N,N-dimethylformamide were mixed evenly at a mass ratio of 1:0.7:9, and stirred at 85°C and 400 r / min for 15 minutes. A catalyst solution with a mass of 2.2 times that of 2-aminoethyl-2-cyanoacetate was uniformly added dropwise within 20 minutes. The mixture was heated to 103°C and stirred for 6.5 hours. The mixture was dried at 65°C for 9 hours under vacuum conditions to obtain a modified polyester.

[0038] (3) The modified polyester and functionalized porous silica microspheres were mixed evenly at a mass ratio of 1:0.07, placed in an internal mixer, stirred at 245°C for 11 minutes, 0.035 times the mass of the modified polyester zinc chloride and 0.07 times the mass of the modified polyester 1,6-dichlorohexane were added and mixed evenly, placed in a mold, and maintained at 235°C and 2.5 MPa for 4 minutes. The pressure was kept constant, cooled to 75°C and kept warm for 35 minutes, naturally cooled to room temperature, and then demolded and taken out to obtain an impact-resistant packaging material.

[0039] Embodiment 3:

[0040] A method for preparing an impact-resistant packaging material, the method comprising the following steps:

[0041] (1) Phenyl dichlorophosphate and (9CI)-[(dimethylamino)methyl]-silanediol were added to acetonitrile (20 times the mass of phenyl dichlorophosphate) in a molar ratio of 1:1, and stirred at 86°C and 500 r / min for 5 hours under nitrogen protection, and dried at 70°C for 10 hours under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant; zinc acetate, diethylene glycol, and deionized water were mixed at a mass ratio of 1:250:12, stirred at 180°C and 500 r / min for 5 minutes, cooled to room temperature, and then allowed to stand for 3 hours to obtain a zinc oxide sol; porous silica microspheres and zinc oxide sol were mixed at a mass ratio of 1:12, ultrasonically dispersed for 30 minutes, and dried at 18 The mixture was stirred at 0°C and 500 r / min for 1 h, centrifuged, washed with anhydrous ethanol and deionized water for 5 times each, and dried at 110°C for 8 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; the porous silica microspheres loaded with zinc oxide and anhydrous ethanol were mixed evenly at a mass ratio of 1:100, ultrasonically dispersed for 60 min, 1.4 times the mass of the porous silica microspheres loaded with zinc oxide as a phosphorus-silicon synergistic flame retardant, and 0.09 times the mass of the porous silica microspheres loaded with zinc oxide as dibutyltin dilaurate were added, and under nitrogen protection, the mixture was stirred at 35°C and 500 r / min for 2 h, filtered, and dried at 60°C for 16 h under vacuum conditions to obtain functionalized porous silica microspheres;

[0042] (2) 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate were mixed uniformly in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.05 times the mass of ethyl acrylate) was added, and the mixture was stirred at 60°C and 500 r / min for 2 h to obtain a terpyridine diester monomer; ethylene glycol, antimony trioxide, trimethyl phosphate, and titanium dioxide were mixed uniformly in a mass ratio of 1:0.04:0.07:0.03, terpyridine diester monomer (0.4 times the molar amount of ethylene glycol) and diethyl benzophenone-4,4'-dicarboxylate (0.6 times the molar amount of ethylene glycol) were added, and the mixture was placed in a polycondensation reactor and heated at 280°C and 500 r / min for 2 h. nStir and react for 1 hour, reduce the pressure to 100Pa, continue to stir and react for 1 hour, cool to room temperature and then discharge, wash with deionized water 5 times, dry at 60°C for 7 hours under vacuum conditions to obtain functionalized polyester; ammonium acetate and glacial acetic acid are mixed evenly at a mass ratio of 1:4 to prepare a catalyst solution; functionalized polyester, 2-aminoethyl-2-cyanoacetate and N,N-dimethylformamide are mixed evenly at a mass ratio of 1:0.8:10, stirred at 90°C and 500r / min for 10 minutes, and a catalyst solution of 2.4 times the mass of 2-aminoethyl-2-cyanoacetate is uniformly added dropwise within 20 minutes, the temperature is raised to 106°C and stirred for 6 hours, and dried at 70°C for 8 hours under vacuum conditions to obtain modified polyester;

[0043] (3) The modified polyester and functionalized porous silica microspheres were mixed evenly at a mass ratio of 1:0.08, placed in an internal mixer, stirred at 250°C for 10 min, 0.04 times the mass of the modified polyester zinc chloride and 0.08 times the mass of the modified polyester 1,6-dichlorohexane were added and mixed evenly, placed in a mold, and maintained at 240°C and 3 MPa for 3 min. The pressure was kept constant, cooled to 80°C and kept warm for 30 min, naturally cooled to room temperature, and then demolded to obtain an impact-resistant packaging material.

[0044] Comparative Example 1:

[0045] The difference between the preparation method of the impact-resistant packaging material of Comparative Example 1 and Example 2 lies in the difference in step (1), where step (1) is modified as follows: zinc acetate, diethylene glycol, and deionized water are mixed uniformly in a mass ratio of 1:245:11, stirred at 175°C and 400 r / min for 6 min, cooled to room temperature and allowed to stand for 2.5 h to obtain zinc oxide sol; porous silica microspheres and zinc oxide sol are mixed uniformly in a mass ratio of 1:11, ultrasonically dispersed for 25 min, stirred at 175°C and 400 r / min for 1.5 h, centrifuged, washed 4 times with anhydrous ethanol and deionized water respectively, and dried at 105°C for 9 h under vacuum conditions to obtain functionalized porous silica microspheres. The remaining steps are the same as those of Example 2.

[0046] Comparative Example 2:

[0047] The preparation method of the impact-resistant packaging material of Comparative Example 2 is different from that of Example 2 in that step (2) is different. Step (2) is modified as follows: ethylene glycol, antimony trioxide, trimethyl phosphate, and titanium dioxide are uniformly mixed in a mass ratio of 1:0.03:0.06:0.025, diethyl terephthalate with a molar amount of 0.35 times that of ethylene glycol and diethyl benzophenone-4,4'-dicarboxylate with a molar amount of 0.55 times that of ethylene glycol are added, and the mixture is placed in a polycondensation reactor, stirred and reacted at 275°C and 400 r / min for 1.5 h, the pressure is reduced to 75 Pa, the stirring reaction is continued for 1.5 h, the material is discharged after cooling to room temperature, and the mixture is used. Wash with deionized water 4 times, dry at 55°C for 7.5h under vacuum conditions to obtain functionalized polyester; mix ammonium acetate and glacial acetic acid at a mass ratio of 1:3.5 to prepare a catalyst solution; mix functionalized polyester, 2-aminoethyl-2-cyanoacetate, and N,N-dimethylformamide at a mass ratio of 1:0.7:9, stir at 85°C, 400r / min for 15min, uniformly add a catalyst solution of 2.2 times the mass of 2-aminoethyl-2-cyanoacetate within 20min, heat to 103°C, stir and react for 6.5h, and dry at 65°C under vacuum conditions for 9h to obtain modified polyester. The remaining steps are the same as in Example 2.

[0048] Comparative Example 3:

[0049] The preparation method of the impact-resistant packaging material of Comparative Example 3 is different from that of Example 2 only in step (2). Step (2) is modified as follows: 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate are mixed uniformly in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (0.04 times the mass of ethyl acrylate) is added, and the mixture is stirred at 55°C and 400r / min for 2.5h to obtain a terpyridine diester monomer; ethylene glycol, antimony trioxide, trimethyl phosphate, Titanium dioxide was mixed evenly at a mass ratio of 1:0.03:0.06:0.025, and 0.35 times the molar amount of ethylene glycol was added to the terpyridine diester monomer and 0.55 times the molar amount of ethylene glycol to diethyl benzophenone-4,4'-dicarboxylate, and placed in a polycondensation reactor, stirred at 275°C and 400r / min for 1.5h, the pressure was reduced to 75Pa, and the stirring reaction was continued for 1.5h, and the material was discharged after cooling to room temperature, washed with deionized water 4 times, and dried at 55°C for 7.5h under vacuum conditions to obtain a modified polyester. The remaining steps were the same as in Example 2.

[0050] Comparative Example 4:

[0051] The preparation method of the impact-resistant packaging material of Comparative Example 4 is different from that of Example 2 only in step (3), and step (3) is modified as follows: the modified polyester and the functionalized porous silica microspheres are mixed uniformly at a mass ratio of 1:0.07, placed in an internal mixer, stirred at 245° C. for 11 min, 0.035 times the mass of the modified polyester zinc chloride is added and mixed uniformly, placed in a mold, maintained at 235° C. and 2.5 MPa for 4 min, the pressure is kept constant, the temperature is reduced to 75° C. and maintained for 35 min, and the mold is removed after natural cooling to room temperature to obtain the impact-resistant packaging material. The remaining steps are the same as those of Example 2.

[0052] Test Example 1

[0053] Impact resistance and anti-aging performance testing

[0054] Test method: The embodiment and the comparative example were prepared into standard specimens according to GB / T1843, and the impact strength of the standard specimens was tested on an impact tester. The standard specimens that were not subjected to the impact test were irradiated with a xenon arc lamp for 72 hours. The impact strength of the standard specimens after UV aging treatment was tested on an impact tester according to GB / T1843. The impact strength change rate of the embodiment and the comparative example before and after UV aging treatment was calculated, and the impact strength change rate = (original impact strength of the specimen - impact strength after UV aging treatment) / original impact strength of the specimen × 100%. The results are shown in Table 1.

[0055] Table 1

[0056]

[0057] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the impact-resistant packaging material prepared by the present invention has good impact resistance and anti-aging performance.

[0058] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the amino group on 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine reacts with the carbon-carbon double bond on ethyl acrylate to prepare a terpyridine diester monomer; ethylene glycol, a terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate are polycondensed to prepare a functionalized polyester, and a terpyridine structure is introduced into the side chain of the functionalized polyester molecule. The terpyridine structure can complex zinc ions to form a cross-linked network, inhibit the relative slip between molecular chains, and give the impact-resistant packaging material excellent impact resistance.

[0059] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Examples 3 to 4, indicating that the functionalized polyester is prepared by polycondensation of ethylene glycol, terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate, and a benzophenone structure is introduced into the main chain of the functionalized polyester molecule; the benzophenone structure introduced into the functionalized polyester is reacted with 2-aminoethyl-2-cyanoacetate to prepare a modified polyester, and an amino group is introduced into the modified polyester molecular chain; the amino group introduced into the modified polyester molecular chain can react with 1,6-dichlorohexane to form a cross-linked network, thereby inhibiting the relative slip between molecular chains and further improving the impact resistance of the impact packaging material.

[0060] By comparison, the impact strength change rate of Examples 1 to 3 is less than that of Comparative Example 3, indicating that ethylene glycol, terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate are polycondensed to prepare functionalized polyester, and a benzophenone structure is introduced into the main chain of the functionalized polyester molecule; the benzophenone structure introduced into the functionalized polyester is reacted with 2-aminoethyl-2-cyanoacetate to prepare a modified polyester, and a derivative of an octocrylene structure is generated on the modified polyester molecular chain; octocrylene belongs to the cinnamic acid compound, and the benzene ring and the carbonyl group in the structure have a conjugated effect, so that it can effectively absorb medium-wave ultraviolet rays, and endow the impact-resistant packaging material with excellent anti-aging properties.

[0061] Test Example 2

[0062] Antimicrobial performance testing

[0063] Test method: The examples and comparative examples were cut into 5mm×10mm×10mm samples and sterilized by ultraviolet irradiation for 3h; the Escherichia coli strains were activated and prepared to a concentration of 3×10 4cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 2.

[0064] Table 2

[0065]

[0066]

[0067] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the impact-resistant packaging material prepared by the present invention has good antibacterial properties.

[0068] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 1 and 4, indicating that phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol are reacted to obtain a phosphosilicate synergistic flame retardant, and Si-H bonds and tertiary amine structures are introduced into the phosphosilicate synergistic flame retardant; the hydroxyl groups on the porous silica microspheres loaded with zinc oxide react with the Si-H bonds on the phosphosilicate synergistic flame retardant to obtain functionalized porous silica microspheres; a tertiary amine structure is introduced into the functionalized porous silica microspheres; the modified polyester, functionalized porous silica microspheres, zinc chloride, and 1,6-dichlorohexane are melt-blended and compression molded to obtain an impact-resistant packaging material; the tertiary amine structure can react with the chlorine on 1,6-dichlorohexane to form a quaternary ammonium salt structure, thereby improving the antibacterial properties of the impact-resistant packaging material.

[0069] Test Example 3

[0070] Flame retardant performance test

[0071] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406.2, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 3.

[0072] Table 3

[0073]

[0074]

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the impact-resistant packaging material prepared by the present invention has good flame retardant properties.

[0076] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol are reacted to prepare a phosphorus-silicon synergistic flame retardant, and Si-H bonds are introduced into the phosphorus-silicon synergistic flame retardant; the hydroxyl groups on the porous silica microspheres loaded with zinc oxide are reacted with the Si-H bonds on the phosphorus-silicon synergistic flame retardant to prepare functionalized porous silica microspheres; phosphorus element and Si-O bonds are introduced into the functionalized porous silica microspheres; the introduction of phosphorus element and Si-O bonds can improve the flame retardant properties of impact-resistant packaging materials.

[0077] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An impact-resistant packaging material, characterized in that: The impact-resistant packaging material is prepared by reacting porous silica microspheres loaded with zinc oxide and a phosphorus silicon synergistic flame retardant to obtain functional porous silica microspheres; polycondensing ethylene glycol, a terpyridine diester monomer, and diethyl benzophenone-4,4'-dicarboxylate to obtain functional polyester; reacting the functional polyester and 2-aminoethyl-2-cyanoacetate to obtain modified polyester; and melt-blending the modified polyester, functional porous silica microspheres, zinc chloride, and 1,6-dichlorohexane, and performing compression molding to obtain the material. The phosphorus-silicon synergistic flame retardant is prepared by reacting phenyl dichlorophosphate and (9CI)-[(dimethylamino)methyl]-silanediol; The porous silica microspheres loaded with zinc oxide are prepared by reacting porous silica microspheres and zinc oxide; The terpyridine diester monomer is prepared by reacting 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate.

2. A method for preparing an impact-resistant packaging material, characterized in that: The method for preparing the impact-resistant packaging material comprises the following preparation steps: (1) Porous silica microspheres and zinc oxide sol are mixed in a mass ratio of 1:(10-12), ultrasonically dispersed for 20-30 min, stirred at 170-180° C. and 300-500 r / min for 1-2 h, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 100-110° C. for 8-10 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; Porous silica microspheres loaded with zinc oxide and anhydrous ethanol are mixed in a mass ratio of 1:(10-12), ultrasonically dispersed for 20-30 min, stirred at 170-180° C. and 300-500 r / min for 1-2 h, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 100-110° C. and 8-10 h under vacuum conditions to obtain porous silica microspheres loaded with zinc oxide; 80-100) were mixed evenly, ultrasonically dispersed for 50-60 min, 1.2-1.4 times the mass of the porous silica microspheres loaded with zinc oxide was added with a phosphorus silicon synergistic flame retardant, 0.07-0.09 times the mass of the porous silica microspheres loaded with zinc oxide was added with dibutyltin dilaurate, and under nitrogen protection, the mixture was stirred at 25-35° C. and 300-500 r / min for 2-3 h, filtered, and dried at 50-60° C. for 16-18 h under vacuum conditions to obtain functionalized porous silica microspheres; (2) Ethylene glycol, antimony trioxide, trimethyl phosphate and titanium dioxide are mixed uniformly in a mass ratio of 1:(0.02-0.04):(0.05-0.07):(0.02-0.03), terpyridine diester monomer in an amount of 0.3-0.4 times the molar amount of ethylene glycol and diethyl benzophenone-4,4'-dicarboxylate in an amount of 0.5-0.6 times the molar amount of ethylene glycol are added, and the mixture is placed in a polycondensation reaction kettle for polycondensation reaction. The mixture is cooled to room temperature and then discharged, washed with deionized water for 3-5 times, and dried at 50-60°C for 7-8 hours under vacuum conditions. Prepare functional polyester; mix the functional polyester, 2-aminoethyl-2-cyanoacetate and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.8):(8-10), stir at 80-90°C and 300-500r / min for 10-20min, uniformly add a catalyst solution of 2-2.4 times the mass of 2-aminoethyl-2-cyanoacetate dropwise within 20min, heat to 100-106°C and stir for reaction for 6-7h, dry at 60-70°C under vacuum for 8-10h to prepare modified polyester; (3) The modified polyester and the functionalized porous silica microspheres are mixed uniformly in a mass ratio of 1:(0.06-0.08), placed in an internal mixer, stirred at 240-250° C. for 10-12 min, 0.03-0.04 times the mass of the modified polyester zinc chloride and 0.06-0.08 times the mass of the modified polyester 1,6-dichlorohexane are added and mixed uniformly, placed in a mold for compression molding, and demolded after naturally cooling to room temperature to obtain an impact-resistant packaging material.

3. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The particle size of the porous silica microspheres in step (1) is 200 to 300 nm.

4. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The preparation method of the zinc oxide sol in step (1) is as follows: zinc acetate, diethylene glycol and deionized water are uniformly mixed in a mass ratio of 1:(240-250):(10-12), stirred at 170-180° C. and 300-500 r / min for 5-7 min, cooled to room temperature and then allowed to stand for 2-3 h to obtain the zinc oxide sol.

5. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The preparation method of the phosphorus-silicon synergistic flame retardant in step (1) is as follows: adding phenyl dichloride phosphate and (9CI)-[(dimethylamino)methyl]-silanediol in a molar ratio of 1:1 to acetonitrile with a mass of 18 to 20 times that of phenyl dichloride phosphate, stirring and reacting at 80 to 86°C and 300 to 500 r / min for 5 to 6 hours under nitrogen protection, and drying at 70 to 80°C for 8 to 10 hours under vacuum conditions to obtain the phosphorus-silicon synergistic flame retardant.

6. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The preparation method of the terpyridine diester monomer in step (2) is as follows: 4-[2,2':6',2"-terpyridine]-4'-yl-benzylamine and ethyl acrylate are uniformly mixed in a molar ratio of 1:2, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene in an amount of 0.03 to 0.05 times the mass of ethyl acrylate is added, and the mixture is stirred at 50 to 60° C. and 300 to 500 r / min for 2 to 3 hours to obtain the terpyridine diester monomer.

7. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The process parameters of the polycondensation reaction in step (2) are: stirring the reaction at 270-280° C., 300-500 r / min for 1-2 hours, reducing the pressure to 50-100 Pa, and continuing to stir the reaction for 1-2 hours.

8. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The preparation method of the catalyst solution in step (2) is: ammonium acetate and glacial acetic acid are mixed uniformly in a mass ratio of 1:(3-4) to prepare a catalyst solution.

9. The method for preparing a shock-resistant packaging material according to claim 2, characterized in that: The process parameters of the compression molding in step (3) are: at 230-240° C., 2-3 MPa, maintaining pressure for 3-5 min, keeping the pressure constant, cooling to 70-80° C. and maintaining the temperature for 30-40 min.

Citation Information

Cited By

  • Flame-retardant corrosion-resistant coating and preparation method thereof

    CN120041039A

  • Composite resin material for 3D printing and preparation method thereof

    CN121006039A

  • Composite resin material for 3D printing and preparation method thereof

    CN121006039B